Alternatif Integrasi Nilai-nilai Islami dalam Pembelajaran IPAS di Sekolah Dasar - Fadhlan, M. Dwi; Ahmad, Saidah; Rusmanto (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze teachers' strategies in integrating Islamic values into Science and Social Studies (IPAS) learning during the implementation of the Merdeka Curriculum at SDN 198 Jambi City. The research employs a qualitative approach with a case study design. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed thematically using the Miles and Huberman model. The findings reveal that the integration of Islamic values occurs systematically through four stages: planning, implementation, evaluation, and learning outcomes. During the implementation stage, integration is realized through conceptual, creed-based, moral, and worship approaches that are internalized in learning activities as well as through teacher role modeling. Supporting factors include religious school leadership, a conducive learning environment, and collaboration among teachers. Meanwhile, inhibiting factors include limited facilities and infrastructure, lack of professional training, and heterogeneity in students' understanding. These findings confirm that the integration of Islamic values in IPAS learning not only enhances students' conceptual understanding but also strengthens their religious character. Thus, this practice aligns with the holistic educational goals of the Merdeka Curriculum